2007
DOI: 10.1002/elan.200603782
|View full text |Cite
|
Sign up to set email alerts
|

Electrooxidation of DNA at Glassy Carbon Electrodes Modified with Multiwall Carbon Nanotubes Dispersed in Chitosan

Abstract: We report on the analytical performance of glassy carbon (GCE) electrodes modified with a dispersion of multiwall carbon nanotubes (CNT) in chitosan (CHIT) for the quantification of DNA. The electroanalytical response of the resulting electrodes was evaluated using differential pulse voltammetry, while the electrochemical reactivity of the film surface was characterized using scanning electrochemical microscopy. Different treatments of the modified GCE were evaluated to improve the stability of the film and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 46 publications
2
41
0
Order By: Relevance
“…Pauliukaite et al conducted a study on the immobilization effectiveness of functionalized carbon nanotubes into CHI using different cross-linking agents and tested the modified electrodes for the determination of hydrogen peroxide. Additionally, in 2007 we reported 25 on the analytical performance of glassy carbon electrodes (GCEs) modified with a dispersion of CNTs in CHI for the quantification of DNA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pauliukaite et al conducted a study on the immobilization effectiveness of functionalized carbon nanotubes into CHI using different cross-linking agents and tested the modified electrodes for the determination of hydrogen peroxide. Additionally, in 2007 we reported 25 on the analytical performance of glassy carbon electrodes (GCEs) modified with a dispersion of CNTs in CHI for the quantification of DNA.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, dsDNA was selected as analytical probe, since CNTmodified electrodes have been widely used to quantify DNA, to evaluate DNA damage and for hybridization studies [25][26][27][28] . We conclude that the GCE/CNT response strongly depends on the length of CNTs, their degree of oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan acts as scaffold for dispersing MWCNT and incorporating firmly MWCNT and biomolecules at different electrodes 37 . In addition, the chemical treatment of MWCNT-CHIT immobilized at carbon electrode surface has been proven to be strongly influencing the adsorption and electrooxidation of DNA, once cross-linked with glutaraldehyde 38 .  Acetic acid-plasma treatment on gold-supported aligned carbon nanotubes, generated from pyrolysis of iron (II) phthalocyanine, followed by grafting single-strand DNA chains with an amino group at the 5' phosphate end [AmC65'→3') onto the plasma-induced -COOH group through the amide formation, in presence of EDC [1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride] coupling agent was developed by Pingang and Liming 39 in order to increase the sensitivity and selectivity.…”
Section: Strategies Used For the Immobilization Of Dna Over Working/mmentioning
confidence: 99%
“…Adenine and guanine residues of DNA can electrochemically be detected with a poor signal and a low sensitivity at various electrodes such as gold, glassy carbon (GC), carbon nanotubes (CNTs), and polymer modified graphite/GC [78][79][80][81][82][83]. From a fundamental point of view, the main problem on evaluating the use of CNTs for electrochemical applications such as sensors and energy storage devices, is the presence of metallic impurities, as the synthesis of nanotubes is usually achieved with the use of metal catalyst.…”
Section: Biosensingmentioning
confidence: 99%
“…For examples, Bollo et al [80], Pedano et al [84] and Nowicka et al [85] found that ds-DNA exhibited weak responses at polished GC electrodes, while two other research groups reported no electrochemical response of ds-DNA at bare GC electrodes [80,86]. Obviously, this points to the fact that the oxidation dynamics of ds-DNA on such electrodes could relate with unknown factors such as the surface roughness, surface functional species, surface area, preferential facets, grain size, electroactive media, time of exposure to air etc, many of which are difficult to be controlled by simple mechanical polishing or electrochemical activation procedures.…”
Section: Biosensingmentioning
confidence: 99%